The Influence of Mood and Customer Satisfaction Towards Purchasing Behavior In Clothing Store (Study in Brawijaya University Student Using Structural Equation Modeling) - Prasasti, Arum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Clothing store is one of the retailers that growing in this recent years, especially in Malang, where there are so many students from many cities around Indonesia. Factors that influencing customer to buy is not just about price. Customer mood and customer satisfaction is expected to have a significant contribution to purchasing behavior. This research is aimed at understanding how customer mood and customer satisfaction influencing purchasing behavior in the clothing store.. There is mood as the independent variable, customer satisfaction as the mediating variable, and purchasing behavior as the dependant variable. This research is an explanatory research, based on the fact that the purpose of this study is to explain the relation and the influence of some pre-determined variables. This study examines undergraduate students in University of Brawijaya in the Faculty of Administration Science, Faculty of Economics and Business, Faculty of Social Sciences and Politics, and Faculty of Law. A questionnaire used to collect data with 200 samples from first until fourth year students in University of Brawijaya selected by probability sampling. The research instruments are tested by validity and reliability test. To analyze the data, Structural equation modeling (SEM) Â that including normality test, outliers, and goodness of fit) are used. The result of this study is that mood and customer satisfactionÂ significantly affects purchasing behavior (dependent variable). Each of the indicator of each variables showing a positive contribution to their own variables. This study also shows respondents generally thought that when making purchases in clothing store they are considering their mood and pre-purchase satisfaction. Keywords: mood, customer satisfaction, purchasing behavior